The Evaluation of the Result of Warm Normal Saline Irrigation in Ureteral Endoscopic Surgeries: A Randomized Clinical Trial - Mohammadzadeh Rezaei, Mohammad Ali; Akhavan Rezayat, Alireza; Tavakoli, Mahmoud; Jarahi, Lida (Urology Journal, 2018)
Purpose: Transurethral lithotripsy (TUL) is a major modality for the endoscopic management of ureteral stones. Ureteral spasm makes access for ureters difficult, which causes impaction of the ureteroscope, ureteral dislodge, and a low success rate of endoscopic surgeries. This study described the outcomes of a new endoscopic surgical experience by use of 40-degree warm saline irrigation during TUL compaired with routine ambient air irrigation in TUL. Materials and methods: In this randomized clinical trial from 2014 to 2015, 150 patients with ureteral stone with balanced randomization were divided into two parallel groups. Patients underwent TUL in the first group with 20–25 degree saline irrigation and in the second group with 40-degree saline irrigation. One surgical team with the same semi-rigid instrument performed all TULs and the other steps were similar in both groups. Complete stone fragmentation was measured as the primary outcome and the duration of procedure, retrograde stone migration and all and any intraoperative complications were the secondary measurements. Result: While comparing warm saline irrigation with cold saline irrigation, the rate of access to upper ureter was 95% versus 72%, stone retropulsion frequency was 10.7% versus 30.7% and the stone-free rate was 96% versus 76% respectively (P < .05). There was no ureteroscope impaction and ureteral dislodge in both groups. Conclusion: Using warm saline irrigation in endoscopic surgeries results in better surgical outcomes including a lower ureteral spasm rate, greater ureteral muscle relaxation and better access to the upper ureteral zone, and a lower rate of complications, such as ureteroscope impaction, ureteral dislodge and stone retropulsion.